Acute Kidney Injury After Repeated Exposure to Contrast Material for Coronary Angiography - Betoko, Aisha (Mayo Clin Proc Innov Qual Outcomes, 2021)
OBJECTIVE: To assess the incidence of contrast-associated acute kidney injury (CAAKI) after repeated exposure to contrast material for computed tomography (CT) and conventional coronary angiography within short intervals. METHODS: We studied 651 patients enrolled in the CorE-64 (November 5, 2005–January 30, 2007) and CORE320 (October 21, 2009–August 17, 2011) multicenter studies. Participants with suspected obstructive coronary heart disease were referred for diagnostic cardiac catheterization and underwent coronary CT angiography for research before invasive angiography. Nonionic, low-osmolality iodinated contrast material was used for all imaging. RESULTS: The median age of the patients was 62 years, and 190 (29%) were women. Major risk factors for acute kidney injury were present in 277 of 651 (43%) patients. The median interval between CT imaging and invasive angiography was 3.1 days (interquartile range, 0.9-8.0 days). The median volume of contrast material was 100 mL for each test. In 16 (2.5%) of 651 patients, CAAKI developed. Of these cases, 1 occurred after the CT scan, whereas 6 were documented after invasive angiography (compared with post-CT creatinine concentration assessment). In 9 patients, CAAKI was found in comparing creatinine concentration after completion of both tests with baseline values (but not compared with post-CT imaging). CONCLUSION: Acute kidney injury after repeated exposure to iodinated contrast media within a few days is uncommon even in a population of patients with highly prevalent risk factors. Withholding of clinically indicated contrast-enhanced imaging may therefore not be justified in this setting.